Unusual vitamin E profile in the oil of a wild African oil palm tree (Elaeis guineensis Jacq.) enhances oxidative stability of provitamin A - Gutbrod, Philipp; Pottier, Delphine; Shirvani, Safoora; Gutbrod, Katharina; Djien-Nyami, Félicité; Emade Ngoudjede, Raïssa; Ngando-Ebongue, Georges; Dörmann, Peter (Frontiers in Plant Science, 2024)
The African Oil Palm (Elaeis guineensis Jacq.) is the predominant oil crop in the world. In addition to triacylglycerols, crude palm oil (CPO) extracted from the mesocarp of the fruits, contains high amounts of provitamin A (carotenes) and vitamin E (tocochromanols). Because of their unsaturated nature, the carotenes are prone to oxidation and therefore are in part limiting for the shelf life of CPO. In the present study, a wild Oil Palm tree (C59) from Cameroon was identified that lacks α-tocopherol and α-tocotrienol and instead accumulates the respective γ forms, suggesting that the activity of γ-tocopherol methyltransferase (VTE4) was affected. Sequencing of the VTE4 locus in the genome of plant C59 identified a G/C polymorphism that causes the exchange of a highly conserved tryptophan at position 290 with serine. The W290S exchange renders the VTE4 enzyme inactive, as shown after expression in Escherichia coli and Arabidopsis thaliana. The oxidative stability of carotenes in the mesocarp of the wild palm C59 was enhanced compared with control accessions. Furthermore, supplementation of commercial palm oil with different tocochromanols showed that γ-tocotrienol exerts a stronger effect during the protection of carotenes against oxidation than α-tocotrienol. Therefore, the introduction of the high γ-tocotrienol trait into elite breeding lines represents a potent strategy to protect carotenes against oxidation and extend the shelf life of CPO, hence allowing the development of new value added of high carotene CPO to be used to fight against vitamin A deficiency.